Contacte lingüístic entre el català i el castellà a la València dels segles XVIII i XIX - Martí Mestre, Joaquim (Caplletra. Revista Internacional de Filologia, 1996)
Joaquim Martí Mestre studies several phenomena of linguistic contact in the valencian context of 18th and 19th centuries, such as linguistic interference, code switching, code mixing, as well as the problem of the functions, conditions and sphere of use of the languages, Catalan and Castilian in this case, and linguistic attitudes and social values related to each language in contact.